The Role of Aesthetics in Shaping Cultural Narratives - Dieudonne, Emmanuel (International Journal of Philosophy, 2024)
Purpose: The general objective of this study was to explore the role of aesthetics in shaping cultural narratives. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive’s time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings reveal that there exists a contextual and methodological gap relating to the role of aesthetics in shaping cultural narratives. Preliminary empirical review revealed that aesthetics significantly influence the formation and perpetuation of cultural narratives across various forms of artistic and cultural expressions. It highlighted how traditional and contemporary aesthetic forms both preserve historical cultural heritage and adapt to societal changes, emphasizing the role of digital aesthetics in modern cultural dynamics. The research underscored the importance of diverse representations to challenge dominant narratives and promote inclusivity. It also emphasized the implications for artists, cultural theorists, educators, and policymakers in recognizing and utilizing the transformative potential of aesthetics in shaping cultural narratives. Unique Contribution to Theory, Practice and Policy: The Semiotics Theory, Social Constructionism and Cultural Hegemony may be used to anchor future studies on the role of aesthetics in shaping cultural narratives. The study recommended expanding theoretical frameworks by integrating interdisciplinary approaches to better understand the role of aesthetics in shaping cultural narratives. Practically, it urged artists and cultural practitioners to critically engage with the cultural symbols in their work, and for educators to incorporate aesthetics and cultural narrative analysis into their curricula. Policy-wise, it emphasized the need for inclusive cultural policies that promote diversity, support digital literacy, and encourage collaboration among stakeholders to create initiatives that celebrate diverse aesthetic expressions.